Inspiration, inoculation, and introductions are all critical to successful mentorship for undergraduate women pursuing geoscience careers - Paul R. Hernandez (Nature Portfolio, 2020)
To retain women in geoscience careers, exposure to role models, training on network growth and introduction to mentors in combination improve outcomes for undergraduates, according to a randomized intervention experiment.